Kekerasan Dalam Rumah Tangga Akibat Perceraian Dan Dampaknya Terhadap Anak - Catur Sakti Artaro (Jurnal Hukum dan Sosial Politik, 2024)
This study aims to describe and understand the impact of domestic violence (DV) on children who are victims or witnesses of violence that occurs in the household. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with 3 respondents consisting of 2 parents who divorced due to domestic violence and 1 child who experienced domestic violence. The data were analyzed using narrative analysis techniques. The results showed that domestic violence has a serious and diverse impact on children, both physically, psychologically and socially. This impact is influenced by several factors, such as the type, frequency, intensity, and duration of violence, age, gender, and characteristics of the child, as well as support and protection provided by other parties. This research provides contributions, implications and suggestions for the development of science, practice and further research.